Centipede envenomation (Chilopoda): Case report - Haddad Junior, Vidal [UNESP]; de Amorim, Paulo Cezar Haddad [UNESP]; da Cruz, Carolina Rassi [UNESP]; Amaral, Antônio Lucas Sforcin [UNESP] (FapUNIFESP (SciELO), 2022)
Centipedes are venomous arthropods that have an elongated body, divided into many segments, presenting a pair of legs in each segment, adapted pairs of paws that simulate fangs and inject venom causing intense pain, with local erythema and edema, and rarely, blisters and skin necrosis. We present the case of a young woman pricked on her upper lip with intense swelling and local pain and discuss the real danger of envenomation and the therapeutic measures that should be taken.
Keywords: Bites and stings; Centipedes envenomation; Chilopoda